2023
DOI: 10.1101/2023.05.24.541839
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Notch-Pdgfrβ axis suppresses brown adipocyte progenitor differentiation in early postnatal mice

Abstract: De novo brown adipogenesis holds potential in combating the epidemics of obesity and diabetes. However, the identity of brown adipocyte progenitor cells (APCs) and their regulation have not been extensively studied. Here through in vivo lineage tracing, we observed that PDGFR beta+ pericytes give rise to developmental brown adipocytes, but not to those in adult homeostasis. In contrast, TBX18+ pericytes contribute to brown adipogenesis throughout both developmental and adult stages, though in a depot-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Moreover, these cells demonstrate the ability to differentiate into beige adipocytes in small clusters under prolonged cold exposure for two weeks; of note, this occurs in multiple waves depending on the extent and time course of cold stress [14]. A recent study focusing on BAT demonstrated that PDGFRβ + PCs gave rise to brown adipocytes at an early stage, but not in adulthood [15].…”
Section: The Hallmarks Of Pericytes: Insights From Lineage-tracing St...mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, these cells demonstrate the ability to differentiate into beige adipocytes in small clusters under prolonged cold exposure for two weeks; of note, this occurs in multiple waves depending on the extent and time course of cold stress [14]. A recent study focusing on BAT demonstrated that PDGFRβ + PCs gave rise to brown adipocytes at an early stage, but not in adulthood [15].…”
Section: The Hallmarks Of Pericytes: Insights From Lineage-tracing St...mentioning
confidence: 99%
“…Likewise, another study demonstrated that TBX18 plays a minor role in de novo beige adipogenesis [54]. However, in BAT, TBX18 + PCs act as progenitors of brown adipocytes in multiple regions, such as thoracic perivascular and supraclavicular depots, but not in intrascapular and periaortic regions, suggesting that TBX18 + PCs contribute to brown adipocytes in a depot-specific manner [15].…”
Section: The Hallmarks Of Pericytes: Insights From Lineage-tracing St...mentioning
confidence: 99%
See 1 more Smart Citation